CONCEPT OF URINE IN BRIHATTRAYI - Kumar, *Bishnu; Singh, Jyoti (International Journal of Ayurveda and Pharma Research, 2017)
From the study of ancient surgical text Sushruta samhita, it becomes evident that the urological problems form an important part of medical sciences. This article reviews the various concept of Mutra in Brihattrayi regarding its characteristics, formation , examination, and use for the diagnosis of various aspects of disease and diseased person . Mutra pariksha as such in systematic way is not described in Brihatrayi. Scattered references are available in these texts related to physiological and pathological state. Based on the informations scattered in various texts pertaining to the abnormalities in respect of odour, colour, quantity etc. urine can be used as important diagnostic tool. The scattered references available in Ayurvedic texts are compiled below in following scheme of Sushrutas Sadhvidha pariksha. Sadhvidha Pariksha includes Panchendriya and Prashna Pariksha.Under this heading, temperature and consistency of urine can be taken into consideration. Thus on the basis of differences in touch only; one can diagnose the disease by observing the changes/abnormality in urine. It can be says that clinical diagnosis of certain diseases depends upon various characteristics of mutra. It is helpful in diagnosing a number of diseases and thus its importance should not be ignored. Urine, like any other substance has its own properties and qualities and can be used rationally for treatment of certain diseases. In Ayurveda properties and uses of human urine and the urine of eight different, animals have been described.Mutra pariksha , properties and uses of urine as such in systematic way is not described in Brihatrayi. It is an attempt to compile the various concept of urine and its properties regarding the diagnosis of various disease which are scattered in Brihattrayi.